Temporal-spatial analysis of hospitalizations for bronchiolitis in Brazil: prediction of epidemic regions and periods for immunization against the Respiratory Syncytial Virus - Edilenia Queiroz Pereira; Márcia Lorena Alves dos Santos; Taqueco Teruya Uchimura; Eniuce Menezes (Sociedade de Pediatria de São Paulo, 2023)
Abstract Objective: Due to the high cost and short term of passive immunization against the respiratory syncytial virus, the main virus causing acute viral bronchiolitis, predicting epidemic regions and epidemic months is extremely important. The objective of this study is to identify both the month when the seasonal peak begins and Brazilian regions and states with the highest incidence of monthly hospitalizations due acute viral bronchiolitis. Methods: Based on data obtained from DATASUS, monthly hospitalization rates due acute viral bronchiolitis were calculated for every 10,000 live births to children under 12 months of age in all Brazilian states and the Federal District between 2000 and 2019. Seasonal autoregressive integrated moving average models were estimated to forecast monthly hospitalization rates in 2020. Results: A higher incidence of hospitalizations was found for male children, especially under six months of age. As for Brazilian regions, between 2000 and 2019, the South region registered the highest incidence of hospitalizations, followed by the Southeast, Midwest, North and Northeast regions, in this order. Considering the seasonal peak, the period between March and July 2020 comprised the highest expected hospitalization rates. Conclusions: Palivizumab is suggested to be started between February/March and June/July for most Brazilian states, with the exception of Rio Grande do Sul, which, in addition to presenting the highest rates of hospitalizations for acute viral bronchiolitis per 10,000 live births, has the longest seasonal peak between May and September.